Határvadászok I.- A M. kir. Honvédség határszolgálata : 1938-39 = Border guards; the border service of the I. - M. Royal Army, 1938-39 - Suba, János (Közép-Európai Közlemények, 2017)
Due to the outer circumstances, the Hungarian border defence got militarised. From 1st October, 1938, the Border Guards got under the control of the Defense Ministry, where they were reorganized to border guard forces and completed border protection along with border guarding. This way the not border protecting forces, who provided border guarding, also merged into the army, under the name ‚border guards’. The development of the army also meant a rise in the headcount. The huge lack of cadres led to the decline of the professional standards. One reason for it was that there was no professional training for offi cers and chiefs. The other was the inappropriate attitude towards border guarding tasks, which were often considered the duty of the police or customs offi cers. As opposed to this, the leadership did their best to increase the professional standards. The aim of this study is to review the conditions and circumstances of the border control in the altered situation.